Evolutionary genomics of the pandemic 2009 H1N1 influenza viruses (pH1N 1v) - Qu, Yanhua (BioMed Central, 2011)
BACKGROUND: A new strain of human H1N1 influenza A viruses was broken out in the April 2009 and caused worldwide pandemic emergency. The present study is trying to estimate a temporal reassortment history of 2009 H1N1 viruses by phylogenetic analysis based on a total 394 sequences of H1N1viruses isolated from swine, human and avian. RESULTS: Phylogenetic trees of eight gene segments showed that viruses sampled from human formed a well-supported clade, whereas swine and avian lineages were intermixed together. A new divergence swine sublineage containing gene segments of 2009 H1N1 viruses was characterized, which were closely related with swine viruses collected from USA and South Korea during 2004 to 2007 in six segments (PB2, PB1, PA, HA, NP and NS), and to swine viruses isolated from Thailand during 2004 to 2005 in NA and M. Substitution rates were varied drastically among eight segments and the average substitution rate was generally higher in 2009 H1N1 than in swine and human viruses (F(2)(,23 )= 5.972, P < 0.01). Similarly, higher d(N)/d(S )substitution ratios were identified in 2009 H1N1 than in swine and human viruses except M2 gene (F(2, 25 )= 3.779, P < 0.05). The ages of 2009 H1N1 viruses were estimated around 0.1 to 0.5 year, while their common ancestors with closest related swine viruses existed between 9.3 and 17.37 years ago. CONCLUSION: Our results implied that at least four reassortments or transmissions probably occurred before 2009 H1N1 viruses. Initial reassortment arose in 1976 and avian-like Eurasian swine viruses emerged. The second transmission happened in Asia and North America between 1988 and 1992, and mostly influenced six segments (PB2, PB1, PA, HA, NP and NS). The third reassortment occurred between North American swine and avian viruses during 1998 to 2000, which involved PB2 and PA segments. Recent reassortments occurred among avian-to-swine reassortant, Eurasian and classical swine viruses during 2004 to 2005. South Korea, Thailand and USA, were identified as locations where reassortments most likely happened. The co-circulation of multiple swine sublineages and special lifestyle in Asia might have facilitated mixing of diverse influenza viruses, leading to generate a novel virus strain.